2007
DOI: 10.1136/adc.2005.088807
|View full text |Cite
|
Sign up to set email alerts
|

Bacteraemia in homozygous sickle cell disease in Africa: is pneumococcal prophylaxis justified?

Abstract: The infrequent isolation of Streptococcus pneumoniae from febrile children with SS disease in this study and in four other studies from Nigeria raises questions on a different spectrum of bacterial causes for bacteraemia in malarial areas. There are several possible explanations for this finding, but the data cast sufficient doubt on the case for pneumococcal prophylaxis for a controlled trial on its effectiveness in that environment to seem justified. These data are necessary to determine its role in African … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
85
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(92 citation statements)
references
References 12 publications
3
85
2
Order By: Relevance
“…In cohort studies conducted in the north, it has been shown that abnormal splenic function (indicated by the presence of pitted red cells in the peripheral circulation) is common by 6 months of age and affects almost half of children by the age of 2 years. 33 Although splenomegaly has been shown to persist until later life in African studies than is seen in the north, [34][35][36] an observation that has been linked to the presence of malaria, 34,35,37 there are no data on splenic function in the African context where the role of the spleen in malaria protection therefore remains unknown. Second, even without malaria, children with SCA are already anemic, and a sudden decline in hemoglobin from such a low baseline value could easily be catastrophic.…”
Section: Discussionmentioning
confidence: 99%
“…In cohort studies conducted in the north, it has been shown that abnormal splenic function (indicated by the presence of pitted red cells in the peripheral circulation) is common by 6 months of age and affects almost half of children by the age of 2 years. 33 Although splenomegaly has been shown to persist until later life in African studies than is seen in the north, [34][35][36] an observation that has been linked to the presence of malaria, 34,35,37 there are no data on splenic function in the African context where the role of the spleen in malaria protection therefore remains unknown. Second, even without malaria, children with SCA are already anemic, and a sudden decline in hemoglobin from such a low baseline value could easily be catastrophic.…”
Section: Discussionmentioning
confidence: 99%
“…18 In Africa, the rarity of isolating S pneumoniae was not properly attributed to inadequate culture techniques, which led to inappropriate skepticism regarding the risks of fatal bacterial infections. 35 This issue was settled by a landmark case-control study from Kenya documenting remarkably elevated risks of bacteremia in children with SCA, including S pneumoniae, non-typhus Salmonella, and H influenzae. 36 By confirming that the etiologies of invasive bacterial infection are similar for children with SCA in Africa, this study provided the rationale for adopting both penicillin prophylaxis and pneumococcal immunization.…”
Section: Implementing Preventive Care Fever and Infectionsmentioning
confidence: 99%
“…Penicillin prophylaxis has played a major role in reducing mortality in developed countries 60 and it is important to find out whether it will be similarly beneficial in African countries where several groups have found that Streptococcus pneumoniae is also a major cause of morbidity and mortality 61,62 whereas others report that it is less common. 63 The growth of research collaborations in sickle cell disease between developing countries and well resourced countries 31,32,[61][62][63] has recently been highlighted as an important tool for improving clinical and diagnostic facilities in developing countries as well as advancing our knowledge of disease pathogenesis.…”
mentioning
confidence: 99%